The earth, the sun, the rain - Color Me Badd; Walden, Narada Michael; Giant Records (United States : Giant Records, 1996)
Contain three versions of the song The Earth, The Sun, The Rain.
CD 1 : Single edit / (3:37) -- Album version / (4:16) -- Alternate edit / (4:02).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English